PENGARUH KEPUASAN KERJA, KUALITAS KEHIDUPAN KERJA DAN PRESTASI KERJA TERHADAP KINERJA GURU DI MTS AL JAMIYATUL WASLIYAH TEMBUNG - Muhammad Ihsan; Syukril Jamil Harahap; Husniati .; Dayatullah .; Masrida . (Manajemen dan Bisnis, 2021)
The formulation  in this study is how the influence ofjob  satisfaction,quality of work life and work achievement on teacher performance.  The purpose of this study was to find out and analyze the effect ofjob  satisfaction, quality of work life and work achievement on teacher performance. This  research  is a  descriptive quantitative research.  Data  collection  techniques  are carried out through interviews,  lists of questions and documentation studies.  The sample in this study  was 67 teachers.   Variables are measured on a Likert scale.   Hypothesis testing using multiple linear regression analysis through F test and t test.Simultaneous   test   results  showed   that  job   satisfaction,   work  quality   and   work achievement  had a significant  effect on  teacher performance variables. In part,  job satisfaction has a positive and significant effecton teacher performance,  quality of work life has a positive and significant effecton teacher performance and work achievement has a positive and significant effect on teacher performance.